2016
DOI: 10.1039/c6ra04655j
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of the Al4B2O9 nanowhisker and their applications in reinforced polyhydroxyalkanoate composites

Abstract: Large quantities of aluminum borate (Al4B2O9) nanowhiskers have been successfully synthesized by sol–gel and post-thermal-treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A constant weight is approximately preserved from 800 to 1000°C, however, two exothermal peaks are observed at about 900 and 970°C; likely correspond to the crystallization of Al 4 B 2 O 9 and Al 18 B 4 O 33 phases by the reactions () and (), respectively . It has been shown that the Al 4 B 2 O 9 phase is unstable and is decomposed to Al 18 B 4 O 33 phase and boron oxide at the higher temperature (approximately 1000°C) )(B2O3)(s)(B2O3)(l2)(Al2O3)(s+)(B2O3)(L(Al4normalB2normalO9))(s9)(Al2O3)(s+2)(B2O3)(L(Al18normalB4normalO33))(s…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A constant weight is approximately preserved from 800 to 1000°C, however, two exothermal peaks are observed at about 900 and 970°C; likely correspond to the crystallization of Al 4 B 2 O 9 and Al 18 B 4 O 33 phases by the reactions () and (), respectively . It has been shown that the Al 4 B 2 O 9 phase is unstable and is decomposed to Al 18 B 4 O 33 phase and boron oxide at the higher temperature (approximately 1000°C) )(B2O3)(s)(B2O3)(l2)(Al2O3)(s+)(B2O3)(L(Al4normalB2normalO9))(s9)(Al2O3)(s+2)(B2O3)(L(Al18normalB4normalO33))(s…”
Section: Resultsmentioning
confidence: 99%
“…The synthesized powders are single‐phase and none of the impurity diffraction peaks are observed, indicating the high‐purity percentage of Al 18 B 4 O 33 . Finally, the weight loss of 3% happens between 1050 and 1200°C which is related to an endothermal peak at about 1150°C, corresponding to the evaporation of residual boron oxide …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation